2020
DOI: 10.1111/ijfs.14880
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics as potential detoxification tools for mitigation of pesticides: a mini review

Abstract: Pesticides play a key role in agriculture and food production by controlling the insects, weeds, plant pathogens and microbial contaminations. Although they are useful in some aspects, their inappropriate application can induce health problems including carcinogenicity, reproductive toxicity, neurodegenerative diseases and disruption of endocrine system. In this respect, efficient strategies should be applied to reduce pesticide residue in foodstuffs. Several methods have been proposed in food processing for r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 81 publications
0
21
0
Order By: Relevance
“…Many bacteria, including the LABs, appear to have the ability to efficiently remove the HMs through two mechanisms: biosorption and bioaccumulation [ 102 , 103 , 104 , 105 ].…”
Section: Functional Properties Of Labmentioning
confidence: 99%
“…Many bacteria, including the LABs, appear to have the ability to efficiently remove the HMs through two mechanisms: biosorption and bioaccumulation [ 102 , 103 , 104 , 105 ].…”
Section: Functional Properties Of Labmentioning
confidence: 99%
“…Probiotics have been found to include pesticide-degrading genes encoded into enzymes with degrading activities such as organophosphorus hydrolases, methyl parathion hydrolases, and organophosphorus acid anhydrases. Gene expression in these microorganisms increased in the presence of pesticides [31]. Studies have shown that pesticides can interact with gut microbiota, affecting the receptor sites of different tissues and organs, destroying the intestinal mucosa and cells that lead to pathological changes [32].…”
Section: Broad Effects On Female and Male Reproductionmentioning
confidence: 99%
“…Population rising and urbanization led to widespread utilization of different kinds of pesticides in agricultural practices during the last century (Mohammadi et al, 2020). However, the occurrence of pesticides residues in different food products is a concern for population health due to their detrimental activity in human body (Cengiz et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Diazinon (O,O-diethyl-O-[2-isopropyl-6-methyl-4-pyrimidinyl] phosphoro thioate), is one of the most commonly used organophosphorus pesticides for plants' pest control via inhibition of acetyl cholinesterase (Mahmoudpoor Moteshaker et al, 2020;Shah & Iqbal, 2010). It is known as a genotoxic, mutatoxic, cytotoxic and neurotoxic compound which is classi ed as probable human carcinogen (Group 2A) by International Agency for Research on Cancer (IARC) (Mohammadi et al, 2020). Diazinon is generally used in agricultural crops including different types of fruits and vegetables like apples (Vera et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation